2006
DOI: 10.1002/uog.2708
|View full text |Cite
|
Sign up to set email alerts
|

Meckel–Grüber syndrome: sonography and pathology

Abstract: Objective To define a specific sonographic pattern for the appearance of the kidneys in fetuses affected by Meckel-Grüber syndrome (MGS). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 17 publications
4
16
0
1
Order By: Relevance
“…The mean gestational age at diagnosis is 19 weeks. 4 However, some reports have suggested an early diagnosis (in the first trimester) may be possible and preferable. 5 , 6 MKS is an invariably fatal disorder, however Gazioglu et al reported an unusual case of MKS with a good outcome initially with appropriate treatment and the infant dying at 7 months of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean gestational age at diagnosis is 19 weeks. 4 However, some reports have suggested an early diagnosis (in the first trimester) may be possible and preferable. 5 , 6 MKS is an invariably fatal disorder, however Gazioglu et al reported an unusual case of MKS with a good outcome initially with appropriate treatment and the infant dying at 7 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…4 Chromosomal analysis has revealed chormosome 17 to be linked to MKS. 10 The mortality of MKS is 100% with IUD or death soon after birth.…”
Section: Discussionmentioning
confidence: 99%
“…The mean gestational age at diagnosis is 19 weeks. 7 In such cases, a-fetoprotein (AFP) levels rise in maternal serum between 11 and 16 weeks of gestation. 3 Chromosome analysis by amniocentesis or chorionic villous sampling is also an important diagnostic method.…”
Section: Meckel Gruber Syndrome 91mentioning
confidence: 99%
“…The mean gestational age at diagnosis is 19 weeks. 10 Its almost always fatal, baby die in utero or shortly after birth due to pulmonary hypoplasia and neonatal renal failure. 11,12 OMIM online article number 24900019 has given list of 12 types of MKS with mutation on gene locus of that particular chromosome.…”
Section: Introductionmentioning
confidence: 99%